Increased acute mortality with chemoradiotherapy for locally advanced head and neck cancer in patients ≥ 70 years. Issue 1 (January 2017) - Strom, Tobin J; Naghavi, Arash O; Trotti, Andy M; Russell, Jeffery; Kish, Julie A; McCaffrey, Judith; Otto, Kristen J; Harrison, Louis B; Caudell, Jimmy J
Abstract: Purpose: Concurrent chemoradiotherapy (CRT) is the standard of care for many sites of locally advanced head and neck squamous cell carcinomas (LAHNC). However, on meta-analysis, the addition of chemotherapy did not improve survival for patients > 70 years. We hypothesized that elderly patients treated with CRT would have increased toxicity without similar improvements in survival. Methods: A single-institution, IRB-approved retrospective study took place from 2005 to 2012 including 369 patients treated with CRT for LAHNC. Multivariate models for death at 3 months and death over time were developed using logistic regression and Cox modeling, respectively. Results: Patients ≥ 70 years were treated less often with concurrent cisplatin dosed every 3 weeks (25.5% vs. 71.4%, respectively) and more often with weekly carboplatin (31.9% vs. 3.4%) than patients < 70 years ( n  = 322; p < 0.001). Patients ≥ 70 years experienced increased toxicity during treatment with more frequently hospitalizations (36.2% vs. 21.1%; p  = 0.02) and a lower rate of PEG removal at last follow-up or death (77.1% vs. 92.9%; p  = 0.004). A higher proportion of patients ≥ 70 years died within 3 months (12.8% vs. 2.8%; p  = 0.001) following CRT. Patients ≥ 70 had an increased risk of death at 3 months following CRT (odds ratio 5.19, 95% CI 1.64–16.41; p  = 0.005) and worse survival over time (hazard ratio 2.30, 95% CI 1.34–3.93; p  = 0.002). Conclusions: Patients ≥ 70 years were more often treated with less toxic chemotherapy, yet experienced higher rates of hospitalization during treatment and increased rates of acute mortality following CRT. The efficacy of chemoradiotherapy for elderly patients should be evaluated in a prospective setting.